Regulation of microglia phagocytosis and potential involvement of exercise - Li, Congqin; Wang, Yong; Xing, Ying; Han, Jing; Zhang, Yuqian; Zhang, Anjing; Hu, Jian; Hua, Yan; Bai, Yulong (Frontiers in Cellular Neuroscience, 2022)
Microglia are considered the main phagocytic cells in the central nervous system, remodeling neural circuits by pruning synapses during development. Microglial phagocytosis is also a crucial process in maintaining adult brain homeostasis and clearing potential toxic factors, which are recognized to be associated with neurodegenerative and neuroinflammatory disorders. For example, microglia can engulf amyloid-β plaques, myelin debris, apoptotic cells, and extracellular harmful substances by expressing a variety of specific receptors on the cell surface or by reprogramming intracellular glucose and lipid metabolism processes. Furthermore, physical exercise has been implicated to be one of the non-pharmaceutical treatments for various nervous system diseases, which is closely related to neuroplasticity and microglia functions including proliferation, activation, and phagocytosis. This review focuses on the central regulatory mechanisms related to microglia phagocytosis and the potential role of exercise training in this process.